Investigation into the applicability of Bond Work Index (BWI) and Hardgrove Grindability Index (HGI) tests for several biomasses compared to Colombian La Loma coal - Williams, Orla; Eastwick, Carol; Kingman, S.W.; Giddings, Donald; Lormor, Stephen; Lester, Edward (Elsevier, 2015)
With increasing quantities of biomass being combusted in coal fired power stations, there is an urgent need to be able to predict the grindability of biomass in existing coal mills, but currently no standard biomass grindability test exists. In this study, the applicability of the Hardgrove Grindability Index (HGI) and Bond Work Index (BWI) as standard grindability tests for biomass were investigated for commercially sourced wood pellets, steam exploded pellets, torrefied pellets, sunflower pellets, eucalyptus pellets, miscanthus pellets, olive cake and Colombian La Loma coal. HGI predicts the behaviour of fuels in vertical spindle mills and BWI for tube and ball mills. Compared to La Loma (HGI of 46), all biomasses tested performed poorly with low HGI values (14–29). Miscanthus pellets had the highest BWI or Wi at 426 kW h/t. Despite similar HGI values, some untreated biomasses showed lower BWI values (Eucalyptus pellets Wi 87 kW h/t, HGI 22) compared to others (sunflower pellets Wi 366 kW h/t, HGI 20). Torrefied pellets had the lowest Wi (16 kW h/t), with La Loma coal at 23 kW h/t. Wood, miscanthus and sunflower pellets exhibited mill choking during the BWI test, as the amount of fines produced did not increase with an increasing revolution count. An approximate correlation between HGI and BWI was found for the biomass samples which did not experience mill choking in the BWI test. Milling results in this paper suggest that biomass pellets should be composed of pre-densified particles close to the target size in order to minimise the energy use in mills and possibility of mill choking. Our findings would also suggest that the BWI is a valid test for predicting the potential for mill choking of biomass in a tube and ball mill. HGI, however, appears to be a poor method of predicting the grindability of biomass in vertical spindle mills. A new standard grindability test is required to test the grindability of biomasses in such mills.